IMPROVING READING COMPREHENSION OF THE TENTH GRADE STUDENTS THROUGH DISCOVERY LEARNING - Gebriela, Delya; Darmawan, Darmawan; Maf'ulah, Maf’ulah; Suriaman, Aminah (Tadulako University, 2025)
The objective of this research was to prove that the Discovery Learning method can improve reading comprehension at the tenth grade students of SMA Bala Keselamatan Palu. This research used quasi-experimental design. The sample of this research were the students of X B as the experimental class which consisted of 22 students and the students of X A as the control class which consisted 22 of students. The data were collected through pre-test and post-test. The result of this research revealed that there was a significant improvement in the score of students taught by using Discovery Learning method. The improvement could be seen from the changes in students score which were previously poor to fair. In other words, the use of Discovery Learning method can improve reading comprehension at the tenth grade students of SMA Bala Keselamatan Palu.